Dynamic Interest Retransmission Interval Method for Congestion Control in NLSR. (July 2020) - Hao, Yuanchen; Xue, Yanming; Li, Tong; Ji, Junwei; Ma, Miaomiao
Abstract: Named data link state routing (NLSR) protocol is widely used in current NDN architecture. Due to the limited bandwidth resources of NDN, in the large-scale network running NLSR, when routing information is frequently updated, resulting in a sudden increase in interactive information and the Interest storm is formed. It will cause congestion of protocol information flow and affect network quality and performance index. NLSR does not take corresponding control measures for its Interest traffic and transmission frequency. Therefore, we propose a method to solve this Interest storm: the exponential regression algorithm is used to dynamically adjust the retransmission interval of Sync Interest and the timeout retransmission Interest quantity detection method is provided to add the flow control. The simulation results show that the congestion control method can adjust the sending quantity and retransmission interval of Interest well according to the network traffic.